Pengaruh Subtitusi Tepung Garut (Maranta arundinaceae L) dan Lama Penyimpanan terhadap Total Mikroba pada Roti Tawar - Saputri, Aisyah Ratna, Dwi Sarbini, S.ST., M.Kes, Pramudya Kurnia, STP, M.Agr (2016)
In Indonesia, bread has become the second staple food after rice. Arrowroot flour can be used as an alternative to substitute wheat flour, as it has supported the formation of dough in bread. Arrowroot flour substitution can decrease water levels since it has low protein level so it can lower the binding ability to water. Bread is a product that is easily damaged by spoilage microorganism. Longer period of storage can cause even greater damage. To determine the effect of arrowroot flour substitution and period of storage to the total microbial count on bread. This study used a completely randomized design with three variations of arrowroot flour substitution factor of 0%, 5%, 10% and period of storage factor of 0, 3, 5 days with two replications. Total Plate Count method and SNI formula were used to calculate the total microbes. Data were analyzed using Kruskal Wallis test. Effect of substitution of arrowroot flour to the total microbial count : 0 day storage (highest in 0% substitution: 7,5x 〖10〗^2 colonies/g), 3 days storage (highest in 0% substitution: 3,2x〖10〗^2 colonies/g), 5 days storage (highest in 0% substitution: 3,7x〖10〗^3 colonies/g). Effect of storage duration to total microbes: the 0% substitution (highest in 5 days storage: 2,5x〖10〗^3 colonies/g), 5% substitution (highest in 5 days storage: 2x〖10〗^3 colonies/g), 10% substitution (highest in 5 days: 3,7x〖10〗^3 colonies/g). There is no effect of arrowroot substitution the total microbial count in 0 days storage (p = 0,56), 3 days storage (p = 0,36), 5 days storage (p = 0,56). No effect of storage period on the total microbial count in 0% substitution (p = 0,1), 5% substitution (p = 0,16), and 10% substitution (p = 0,1).